Pathological Evidence for Residual SARS-CoV-2 in the Micrometastatic Niche of a Patient with Ovarian Cancer - Takuma Hayashi; Kenji Sano; Nobuo Yaegashi; Ikuo Konishi (Current Issues in Molecular Biology, 2022)
In previous clinical studies, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in cancer patients has a high risk of aggravation and mortality than in healthy infected individuals. Inoculation with coronavirus disease 2019 (COVID-19) vaccine reduces the risk of SARS-CoV-2 infection and COVID-19 severity. However, vaccination-induced anti-SARS-CoV-2 antibody production is said to be lower in cancer patients than in healthy individuals. In addition, the rationale for why the condition of patients with cancer worsens with COVID-19 is not well understood. Therefore, we examined the infection status of SARS-CoV-2 in the primary tumor and micrometastasis tissues of the patient with cancer and COVID-19. In this study, the expression of angiotensin-converting enzyme 2 (ACE2) was observed, and SARS-CoV-2 particles was detected in ovarian tissue cells in contact with the micrometastatic niche of the patient with high-grade serous ovarian cancer. We believe that the severity of COVID-19 in patients with cancer can be attributed to these pathological features. Therefore, the pathological findings of patients with advanced and recurrent ovarian cancer infected with SARS-CoV-2 may help decrease COVID-19 severity in patients with other cancer types.